Discounting in the Presence of Scarce Ecosystem Services - Xueqin Zhu; Sjak Smulders; Aart de Zeeuw (Center for Economic Studies and ifo Institute (CESifo), 2019)
Discounting has to take account of ecosystem services in consumption and production. Previous literature focuses on the first aspect and shows the importance of the relative price effect, for given growth rates of consumption and ecosystem services. This paper focuses on intermediate ecosystem services in production and shows that for limited substitutability and a low growth rate of these ecosystem services, the growth rate of consumption, and thus the discount rate, declines towards a low value. Using a Ramsey optimal-growth framework, the paper distinguishes three cases. If ecosystem services can be easily substituted, then the discount rate converges to the usual value in the long term. Secondly, if ecosystem services can be easily substituted in production but not in consumption, the relative price effect is important. Finally, and most interestingly, if ecosystem services cannot be easily substituted in production, the discount rate declines towards a low value and the relative price effect is less important. Another part of the previous literature has shown that a declining discount rate is the result of introducing several forms of uncertainty, but this paper reaches that conclusion from an endogenous effect on the growth rate of the economy.
Keywords: C61; D90; E43; O44; Q57; 330; discount rate; ecosystem services; consumption value; production value; growth rate; Ramsey optimal balanced growth